People's Economy in Bali: A Literature Review - Permana, I Putu Hendika; Wiyata Putra, I Dewa Putu Gede; Kurnia Dewi Sutedja, D.A. Gladysia Sistadanta (Indonesia Auditing Research Journal, 2024)
The People's Economic System based on the values of the people and justice encourages the Indonesian people to participate in capital ownership. Cooperative Institutions, Village-Owned Enterprises, Regional Credit Institutions, Cooperatives, and Tourism Villages, most of whose capital is owned by the local community, can be evidence that the People's Economic System applies in Bali. The people's economy in Bali is a concept of economic development that emphasizes the empowerment of local communities and environmental sustainability. The purpose of this study is to focus on the concept of the People's Economic system in empowering regional financial institutions in Bali. The research method used is a literature study, with secondary data in the form of scientific articles and applicable regulations as data sources. Empowerment of financial institutions based on the People's Economic system is expected to be a priority in increasing national development. With the ideological spirit of the People's Economic system from stakeholders, regional financial institutions can develop and be able to help improve the economy in Bali